Professional Competence of Teachers in Improving Learning Effectiveness in Natural and Social Sciences Subjects - Murni, Seri; Fitrah, Hariki; Rahmi Novalita, Rahmi Novalita (Sumatra Journal of Disaster, Geography and Geography Education, 2025)
: This study used a qualitative method. The research setting was conducted at Pegasing 15 Elementary School, Central Aceh Regency. The informants in the study were key informants consisting of natural science and social science subject teachers at Pegasing 15 Elementary School, Central Aceh Regency. The informant sampling technique used the snowball sampling technique. Data collection techniques through observation, interviews, and documentation. Data analysis techniques used data reduction, data display, and drawing conclusions. The results of the study showed that; 1) The professional competence of teachers in mastering learning materials has been implemented well. Mastery of the material is carried out by preparing a learning plan, preparing learning materials according to competency, student needs, and preparing learning materials from various sources, 2) The professional competence of teachers in using media has been implemented well through the use of various learning media, such as visual media, audio media, and audiovisual media. 3) The professional competence of teachers in using learning methods has been implemented well, where teachers have used a variety of learning methods so that effective learning is created.